Application of Response Surface Methodology for Mortar Compressive Strength Containing Glass Powder and Eggshell Powder - Adanu, Olekwu Jessica; Olubunmi, Adetoye; Olubajo, Olumide Olu (Journal of Multidisciplinary Research Advancements, 2024)
This research investigates the impact of Glass Powder (GP) and Eggshell Powder (ESP) on the strength properties of various ternary cement blends, focusing particularly on mortar strength. The study explores the possibility of utilizing industrial waste as a viable replacement for Portland Limestone Cement in response to the growing environmental concerns and the increased energy requirements of non-renewable construction materials. In recent times, the application of waste materials such as GP and ESP in the concrete industry has gained considerable attention due to the associated environmental benefits and to manage the accumulation of these materials. Both GP and ESP contain substantial silica content, making them prospective materials for cement substitutes. The study specifically explores the combined effect of these materials on cement blends, which could potentially improve the cement's properties by mitigating some undesirable effects. In line with this, several tests, including X-ray fluorescence (XRF) were performed on the sample materials to understand their inherent properties and potential interaction when combined in cement blends. The mechanical properties of the resultant mortar were also examined. Using the response surface methodology via Central Composite Design (CCD), the study identified the optimal blending ratio, replacement level, and curing age for the cement blend. A blending ratio of 0.75, a replacement level of 8 wt.%, and a curing age of approximately 60 days resulted in a mortar compressive strength of 41.53N/mm2. The study found that curing age significantly influenced the strength gain attributed to an increase in the hydration reaction time during curing from 3 to 60 days. These findings suggest that using GP and ESP as partial replacements for cement could not only alleviate environmental burdens but also yield significant strength gain in mortar, underlining the promise of these materials in sustainable construction practices. Future research is encouraged to validate these findings and explore large-scale, real-world applications of this approach.